An Electronic Nose system for aromatic rice classification - Abu Hassan, Abdullah; Abdul Hamid, Adom, Prof. Madya Dr.; Ali Yeon, Md. Shakaff, Prof. Dr.; Mansur N, Ahmad; Ammar, Zakaria; Nazifah, Ahmad Fikri; Othman, Omar (American Scientific Publishers, 2011)
Link to publisher's homepage at http://www.aspbs.com/